Regulations and Ethical Codes for Clinical Cell Therapy Trials in Iran. Issue 2 (December 2015) - Saberi, Hooshang; Derakhshanrad, Nazi; Arjmand, Babak; Ai, Jafar; Soleymani, Masoud; Hamidieh, Amir Ali; Joghataei, Mohammad Taghi; Khan, Zahid Hussain; Razavi, Seyed Hassan Emami
Objective: The local regulations for conducting experimental and clinical cell therapy studies are dependent on the national and cultural approach to the issue, and may have many common aspects as well as differences with the regulations in other countries. The study reflects the latest national aspects of cell therapy in Iran and relevant regulations. Methods: The following topics are discussed in the article including sources of cell harvest, regulations for cell disposal, stem cell manufacturing, and economic aspects of stem cell, based on current practice in Iran. Results: All cell therapy trials in Iran are required to strictly abide with the ethical codes, national and local regulations, and safety requirements, as well as considering human rights and respect. Adherence to these standards has facilitated the conduct of human cell therapy trials for research, academic advancement, and therapy. Conclusions: The cell therapy trials based on the aforementioned regulations may be assumed to be ethical and they are candidates for clinical translations based on safety and efficacy issues.